Stress corrosion cracking failure of a SS 316L high pressure heater tube. (August 2018) - Ananda Rao, M.; Sekhar Babu, R.; Pavan Kumar, M.V.
Abstract: A service failure by environmentally induced cracking in austenitic stainless steel 316 L is presented in this work. Extensive research has been carried out on stress corrosion cracking of different materials and environment combinations by various established experimental procedures. The list of alloy/environment combination that causes stress corrosion cracking is continuously increasing. Stress corrosion cracking is a great concern in corrosion resistant alloys exposed to aggressive environments. Stainless steel 316 L material used as high pressure water heater tube failed by stress corrosion cracking was evaluated by various metallurgical characterisation techniques. Results and apparent causes leading to failure were explained in detail. Highlights: High pressure heater tube failure investigated Stress corrosion cracking due to chlorine and caustic corrosion responsible for failure Intergranualar and branched cracking is systematically analyzed and correlated.